Mosapride for gastroesophageal reflux disease in neurologically impaired patients. Issue 3 (13th November 2016) - Komura, Makoto; Kanamori, Yutaka; Tanaka, Yujiro; Kodaka, Tetsuro; Sugiyama, Masahiko; Terawaki, Kan; Suzuki, Kan; Iwanaka, Tadashi
Abstract: Background: The prokinetic agent cisapride is effective for the treatment of gastroesophageal reflux disease (GERD) in infants and children, but is no longer used for this purpose because of safety concerns. Therefore, other pharmacological agents need to be investigated for efficacy in GERD treatment. In this study, we examined the effectiveness and safety of mosapride for the treatment of neurologically impaired children and adolescents with GERD. Methods: Mosapride (0.3 mg/kg/day) was administered to 11 neurologically impaired patients with GERD (five male; median age, 12.3 years). Esophageal acid exposure was measured using esophageal pH monitoring before and at >5 days after the start of mosapride treatment. The pressure and length of the lower esophageal sphincter were compared before and after mosapride treatment. Results: In the 11 patients, median reflux index (percentage of the total monitoring period during which recorded pH was <4.0) was 17.5% (range, 4.4–59%) before and 8.2% (range, 2.8–20.7%) after mosapride treatment ( P = 0.02). Median esophageal clearance was 1.0 min/reflux (range, 0.5–2.1 min/reflux) before and 0.7 min/reflux (range, 0.4–1.2 min/reflux) after treatment with mosapride ( P = 0.02). The median number of reflux episodes before (219) and after (122) drug treatment did not differ significantly. Conclusion: The decreased reflux index in neurologically impaired patients with GERD is due to mosapride, therefore mosapride may be a candidate for GERD treatment.